Promoting university–industry collaboration in Malaysia: stakeholders’ perspectives on expectations and impediments - Norzaini Azman; Morshidi Sirat; Vincent Pang; Yew, Meng Lai; Anantha Raman Govindasamy; Wardatul Akmam Din (2019)
University–Industry Collaboration (UIC) has been identified as an essential item on Malaysia’s agenda for transforming itself into knowledge and innovation-based economy. However, despite the efforts, most initiatives have had limited results. This paper reports on an explorative study that sought to understand the contemporary realities of UIC in the Malaysian context. In particular, the study identified the expectations and impediments to UIC, from the perspectives of three groups of stakeholders – the academics, the industry players and policymakers. The findings reveal a number of barriers, including cultural differences, perceived lack of academic expertise and reputation, an inadequacy of institutional policies and regulations, lack of trust, issues of intellectual property rights, and the lack of an appropriate reward system. This paper concludes by proposing policy recommendations and strategies that could be used by the government, university, and the industry to promote further and foster university-industry collaborative opportunities and initiatives.